Entrepreneurial intentions among University’s students in Malaysia - Raazi, A. *; Farkad, M.; Tehseen, Shehnaz *; Qureshi, Zuhaib Hassan; Jannat, U. M. (2010)
The issue of employability is rising year by year, and Malaysia is also taking it as a serious challenge. The Malaysian government has carried out various initiatives to address the issue of employability; conversely, one of them was successfully promoting the development of entrepreneurship by increasing entrepreneurial courses for instance. The intention was to increase the entrepreneurial intentions amongst university's students to create job opportunities for themselves which could lead to a boost for a developing nation's economy as well. However, the government's initiatives did not succeed as they were expected. The main reason for it ending as a flopped plan was due to failing to identify an individual's intentions. Therefore, the primary purpose of this research is to inspect the Malaysian universities student's intention of being an entrepreneur because, without intention, they might not even consider the option of initiating their own business. This research adapted and integrated the two most common models of examining the entrepreneurial intention, i.e, Theory of Planned Behaviour ('TPB') by Ajzen and Shapero and Sokol's model of an Entrepreneurial Event ('SEE'). This is a quantitative study and a total of 160 students from different Malaysian universities were surveyed using non-probability sampling techniques and by a well-established instrument with the standardized questionnaire, to examine hypothesized relationships. SPSS was used for analyzing the demographic profile and SMART-PLS was utilized for testing the developed hypotheses. The results show that attitude, subjective norms, and perceived behavioural control positively affect the perceived desirability as well as perceived feasibility. Moreover, perceived desirability and perceived feasibility are also positively associated with an entrepreneurial intention. Furthermore, perceived desirability is found as a mediator for the relationship among predictors of entrepreneurial intention but perceived feasibility fails to mediate the association of subjective norm and entrepreneurial intention. By understanding the background of university student's intentions towards entrepreneurship, the Malaysian government and organizations can better present themselves in formulating better initiatives to stimulate and encourage youth to have entrepreneurial intentions in order to initiate their own business. This study also offers some useful managerial implications using the advanced technique of IPM to enhance the H1 H2 H3 H6 H5 H4 H7 H8 performance of critical factors that contribute towards entrepreneurial intentions.